Community health volunteers challenges and preferred income generating activities for sustainability: a qualitative case study of rural Kilifi, Kenya - Adelaide M Lusambili; Njeri Nyanja; Sophie Vusha Chabeda; Marleen Temmerman; Lucy Nyaga; Jerim Obure; Anthony Ngugi (BMC, 2021)
Abstract Background There is a global emphasis on engaging community health volunteers (CHVs) in low- to middle-income countries (LMICs) to reach to the vast underserved populations that live in rural areas. Retention of CHVs in most countries has however been difficult and turnover in many settings has been reported to be high with profound negative effects on continuity of community health services. In rural Kenya, high attrition among CHVs remains a concern. Understanding challenges faced by CHVs in rural settings and how to reduce attrition rates with sustainable income-generating activities (IGAs) is key to informing the implementation of contextual measures that can minimise high turnover. This paper presents findings on the challenges of volunteerism in community health and the preferred IGAs in rural Kilifi county, Kenya. Methods The study employed qualitative methods. We conducted 8 key informant interviews (KIIs) with a variety of stakeholders and 10 focus group discussions (FGDs) with CHVs. NVIVO software was used to organise and analyse our data thematically. Results Community Health Volunteers work is not remunerated and it conflicts with their economic activities, child care and other community expectations. In addition, lack of supervision, work plans and relevant training is a barrier to delivering CHVs' work to the communities. There is a need to remunerate CHVs work as well as provide support in the form of basic training and capital on entrepreneurship to implement the identified income generating activities such as farming and events management. Conclusions Strategies to support the livelihoods of CHVs through context relevant income generating activities should be identified and co-developed by the ministry of health and other stakeholders in consultation with the CHVs.